FORME DI TESTUALITÀ BREVE NELLA DIDATTICA DELL’ITALIANO (Italiano LinguaDue, 2023)
Il contributo parte dal concetto di ‘brevità’ testuale e si concentra sulla nuova “semiosfera testuale”, in particolare su alcuni generi testuali brevi digitati e sul loro possibile uso nella didattica dell’italiano (tweet, blog, email ecc.). Particolare attenzione è dedicata alla email di tipo formale (studente > docente), genere purtroppo poco o per nulla praticato a scuola come dimostrano le molte email di studenti, linguisticamente e pragmaticamente fallimentari.  Forms of short textuality in Italian teaching This paper, starting from the concept of textual 'brevity', focuses on the new "textual semiosphere", in particular on some short typed textual genres and their possible use in L1 Italian didactics (tweet, blog, email etc.). A specific attention is dedicated to the formal email (from the student to the teacher), an unfortunately little or not practiced textual genre at school, as evidenced by the many emails from the students, which are linguistically and pragmatically not-functional short texts.